2006
DOI: 10.1243/14644207jmda92
|View full text |Cite
|
Sign up to set email alerts
|

Effects of material morphology and processing conditions on the characteristics of hydroxyapatite and high-density polyethylene biocomposites by selective laser sintering

Abstract: Hydroxyapatite (HA), a ceramic to which bone inherently bonds, incorporated into a polymer matrix enhances the bioactivity of implants. In order to rapid-manufacture bioactive implants, selective laser sintering (SLS) has been used to fabricate HA and high-density polyethylene (HDPE) composite (HA -HDPE). The properties of SLS-fabricated specimens have been investigated. The main aspects to be considered in the SLS technology are the properties of the materials used in the process and processing parameters (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Strut thickness was seen to increase quadratically as scan spacing decreased. Similar findings -an increase in part dimensions with in-creased delivered energy density -were reported by Hao et al and Caulfield et al [11,20]. As delivered energy density is determined by scan spacing and laser fill power, it was anticipated that the interaction effect of these two parameters would be significant.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Strut thickness was seen to increase quadratically as scan spacing decreased. Similar findings -an increase in part dimensions with in-creased delivered energy density -were reported by Hao et al and Caulfield et al [11,20]. As delivered energy density is determined by scan spacing and laser fill power, it was anticipated that the interaction effect of these two parameters would be significant.…”
Section: Discussionsupporting
confidence: 74%
“…Some groups were able to directly fabricate bioceramic bone implants using an experimental SLS system [2,3], however, to process bioceramics a thermoplastic polymer functioning as a binder material is usually required, as the lasers used in typical commercial SLS systems are unable to fuse ceramic particles together. Several biocompatible polymers have been used for SLS fabrication of scaffolds, including polyethylene, polyetheretherketone, polycaprolactone, polylactide glycolide, polyvinyl alcohol and their composites with hydroxyapatite and other bioceramics [4][5][6][7][8][9][10][11][12]. However, much of this research has only demonstrated the feasibility of fusing powder particles together, and not the fabrication of complex predesigned 3D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include ceramic-glass composites [106][107][108][109][110][111] and ceramic-polymer composites. [112][113][114][115][116] Here, the low-melting glass/ polymer provides densification due to the liquid phase formation. Most of these studied material systems are biocompatible and/or bioactive and designated for biomedical applications that require biocompatibility of materials and complex shapes of products as key mechanical properties.…”
Section: Indirect Slsmentioning
confidence: 99%
“…Polymer powders and ceramic are mixed and laser sintered to form the composite, e.g. PCL and HA [215], PEEK and HA [192], PE and HA [70,165], PA and nano-clay [84], PA and HA [166,167] etc. [29,211].…”
Section: 51mentioning
confidence: 99%